2021
DOI: 10.1111/geb.13266
|View full text |Cite
|
Sign up to set email alerts
|

What drives study‐dependent differences in distance–decay relationships of microbial communities?

Abstract: Aim Ecological communities that exist closer together in space are generally more compositionally similar than those far apart, as defined by the distance–decay of similarity relationship. However, recent research has revealed substantial variability in the distance–decay relationships of microbial communities between studies of different taxonomic groups, ecosystems and spatial scales and between those using different molecular methodologies (e.g., high‐throughput sequencing versus molecular fingerprinting). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 88 publications
3
54
0
Order By: Relevance
“…Geographical distance was generated using the ‘geosphere’ package ( https://cran.r-project.org/web/packages/geosphere/index.html ). The relationship between Bray-Curtis dissimilarity of microbial communities [ 94 ] involved in DMSP/DMS cycling and geographic distance or water depth were analysed using the Mantel test. Alpha-diversity analysis was performed on polar microbiota involved in DMS/DMSP cycling.…”
Section: Methodsmentioning
confidence: 99%
“…Geographical distance was generated using the ‘geosphere’ package ( https://cran.r-project.org/web/packages/geosphere/index.html ). The relationship between Bray-Curtis dissimilarity of microbial communities [ 94 ] involved in DMSP/DMS cycling and geographic distance or water depth were analysed using the Mantel test. Alpha-diversity analysis was performed on polar microbiota involved in DMS/DMSP cycling.…”
Section: Methodsmentioning
confidence: 99%
“…Determining co-assemblies using metagenomic distances In (13), the authors studied the abundance of diazotrophic bacteria in oceanic surface metagenomes and showed that nitrogen fixation is an important feature of the prokaryotic communities living in ocean surface. As microbial genetic distances often co-vary with geographic distances in several habitats (27), co-assemblies were performed based on the geographic coordinates of the metagenomes, i.e. metagenomes belonging to the same oceanic region were co-assembled.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning microorganisms, a large proportion of studies that investigate the effect of connectivity on microorganisms focus on habitat isolation, the inverse of structural connectivity, using the Euclidean distance, assuming that the landscape matrix does not matter. These studies generally report the well‐known distance‐decay pattern predicted by the biogeography theory (see Clark et al 2021 for a meta‐analysis). For instance, Peay et al (2010) used two types of metrics to test the effects of connectivity on fungal species richness on a single tree species, including distance to the mainland and distance to the nearest individual.…”
Section: Modeling Connectivity In Microorganisms: From Biogeography T...mentioning
confidence: 89%